2021
DOI: 10.1111/jan.15068
|View full text |Cite
|
Sign up to set email alerts
|

Constructing the advanced nurse practitioner identity in the healthcare system: A discourse analysis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 27 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…This paper presents an analysis of how the ANP system interacts with the wider healthcare system and how the systemic processes that characterize it both enable and constrain the ANP role. The findings from this paper build on and extend the findings that were reported in previously published papers exploring the discursive construction of ANPs in the Irish health system (Thompson & McNamara, 2022a, 2022b). ANP participants emphasized the need for more power, more professional autonomy and independent practice.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This paper presents an analysis of how the ANP system interacts with the wider healthcare system and how the systemic processes that characterize it both enable and constrain the ANP role. The findings from this paper build on and extend the findings that were reported in previously published papers exploring the discursive construction of ANPs in the Irish health system (Thompson & McNamara, 2022a, 2022b). ANP participants emphasized the need for more power, more professional autonomy and independent practice.…”
Section: Discussionsupporting
confidence: 83%
“…This was an interpretive descriptive study. The data collected and reported here were part of a study exploring the discursive construction of ANPs in the Irish health system (Thompson & McNamara, 2022a, 2022b). In‐depth interviews and focus groups were undertaken to explore how ANPs are positioned within current nursing and health system structures and how these structures construct the ANP role and enable and constrain it.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…An integrative review of professional identity and registered nurses found their self-perception, role and working context needed to be closely aligned to decrease levels of 'stress, tension and uncertainty' (Rasmussen et al, 2018), supporting the experience of APNs in this study. Novice APNs could avoid perceiving themselves as medical substitutes by reframing their identity as professionals in their own right (Thompson & McNamara, 2022), empowering them to become collaborative and equitable practitioners within interprofessional teams. There is ample evidence to support the introduction of more APN roles, with a recent review of 44 systematic reviews of 460 primary studies finding equal or improved outcomes for care provided by NPs compared to settings without an NP (Furness et al, 2020;Kilpatrick et al, 2023).…”
Section: Structural Challenges To Csmentioning
confidence: 99%
“…This is an example of a successful nurse-led clinic. Nurse-led clinics have emerged internationally as an ideal means to achieve improved organisation and efficiency in health services (Randall et al, 2017, House of the Oireachtas, 2018; Torrens et al, 2020), with associated high levels of patient satisfaction (Molassiotis et al, 2020, Linedale et al, 2020), and potential cost-savings (Thompson & McNamara, 2021).…”
Section: Introductionmentioning
confidence: 99%